Expert System for Identification of Red Pepper Plant (Capsicum annum L.) - Sitti Eha Faihah; Kudang Boro Seminar; Suryo Wiyono (PERTETA, 1999)
Identification of plant disease is an important step to decide how it will control. This paper discusses the design and development of an expert system for identification of 12 general diseases of red pepper plant (Capsicum annum L.). Disease identification in this software system was based on the visual symptom of disease(s) in various plant growth stages, similar to the standard rules in plant protection science. The prototype of this software system was implemented by EXSYS Professional for Microsoft Windows (WINEXSYS) version 5.0 and worked under Windows '95 operation system. This software system is user-friendly and equipped by image-visualization that describe disease symptoms.